Componentes espaciais, sociais e culturais em fotografias de Cuibá (MT) na década de 1920: subsídios para a leitura documental de imagens - Mattos, Terezinha de [UNESP] (2008)
The aim of this research is to analyse photographs from the city of Cuiabá in the 1920´s. The proposal of this analysis is based on readings, identifying and representing, by means of summarizing and describing so that informative content related to the socio-historical and cultural context of the city can be recuperated using underlying images. The analysis was carried out using twenty photographs grouped into different thematic sets which range from the architectural monuments, public and private spaces, family portraits, means of transportation, fashion and leisure. Among the results obtained, and theoretical discussions provided by the bibliography, are analyses which show the possibilities of procedure both in relation to summarized texts from readings of the images, as well as denotative and connotative descriptions which represent the content of the images. Taking this into account, this work can contribute to the conservation of local social memories, as well as Information Science, more specifically dealing with information in terms of carrying out an approach and a proposal of methodological procedures, which can help with dealing with information and photograph collections.